Frequencies of HLA-B alleles in Indonesian Malay Ethnic - Rika Yuliwulandari; Kinasih Prayuni; Kencono Viyati; Surakameth Mahasirimongkol; Nuanjun Wichukchinda (Heliyon, 2024)
Background: The HLA-B alleles have been used as a marker to predict drug-induced adverse reactions and as a major contributor to hypersensitivity reactions. We examined the feasibility of HLA-B alleles as pharmacogenomic markers of drug-induced hypersensitivity in an Indonesian Malay Ethnic. Methods: Fifty-eight Indonesian individuals of Malay ethnicity were enrolled in this study. HLA-B alleles were determined using reverse sequence-specific oligonucleotide probe coupled with xMAP technology. Results: HLA-B*15:02 (15.52%), HLA-B*35:05 (9.48%), and HLA-B*07:05 (7.76%) were frequent alleles in the Indonesian Malay ethnic populations. We discovered at least eight pharmacogenomics markers of drug-induced hypersensitivity: HLA-B*15:02, HLA-B*15:21, HLA-B*13:01, HLA-B*35:05, HLA-B*38:02, HLA-B*51:01, HLA-B*57:01, and HLA-B*58:01. HLA-B*15:02 was in the same serotype group with HLA-B*15:21, which is a B-75 serotype associated with genetic predisposition for carbamazepine-induced Stevens–Johnson syndrome and toxic epidermal necrolysis. The Indonesian population, represented by Malay, Javanese, and Sundanese ethnicities, was similar to South East Asian, Han Chinese, and Taiwanese populations based on HLA-B*15:02 frequency as the most common allele found in Malay ethnics. Conclusion: We provided valuable information on the frequency of drug hypersensitivity-associated HLA-B alleles in Indonesian Malay ethnic population, which can improve treatment safety.